ICCREM 2015 : environment and the sustainable building : proceedings of the 2015 International Conference on Construction and Real Estate Management, August 11-12, 2015, Luleå, Sweden - Wang, Yaowu; Olofsson, Thomas, 1952-; Shen, Qiping; Bai, Yong (American Society of Civil Engineers, 2015)
This collection contains 132 peer-reviewed papers on issues of common interest to the construction and real estate management industries. Topics include: global construction management; information technology applications in construction; sustainable construction and innovation; land use and urban management; project and risk management; real estate investment, finance, and management; construction and facility management; and infrastructure construction and management. These papers will be of interest to construction professionals, researchers, planners, contractors, and banking and government officials. --